Correlation of Stunting Incidents with Provision of Iron Supplement Tablets at Kawalu Health Center, Kawalu District, Tasikmalaya City, West Java Province - Zeny Dermawan; Sri Setiatjahjati; Iing Mursalin; Puput Dani Karlina (International Journal of Health and Social Behavior, 2025)
Stunting is a public health problem caused by chronic malnutrition and recurrent infections, especially in toddlers. This study aims to analyze the relationship between giving additional blood supplements (TTD) during pregnancy and the incidence of Stunting in toddlers at the District Health Center, Tasikmalaya West Java. The research used a correlational design with a cross-sectional approach on 133 respondents from pregnant women and toddlers aged 24–35 months. The research results showed that 52.6% of toddlers experienced Stunting, while 72.2% of mothers did not comply with taking TTD during pregnancy. Data analysis using the Chi-Square test did not find a significant relationship between adherence to TTD consumption and the incidence of Stunting (p-value = 0.568). This study emphasizes the importance of a holistic approach in dealing with Stunting, including nutritional education, pregnancy monitoring, and increasing awareness of the importance of consuming TTD.